Value, Growth and Divergence of Opinion in Emerging Markets: Chinese Evidence - Li, Man; Dempsey, Mike (Archives of Business Research, 2017)
The issue of whether value stocks outperform growth stocks as predicted by the Fama and French three-factor model is of continuing interest and debate. In this paper, we examine (a) whether value stocks outperform growth stocks in a developing market (the Shanghai and Shenzhen stock exchanges in their formative years) and (b) whether such outperformance can be attributed to a risk factor as captured by analysts’ divergence of opinion. We establish two major findings. First, we show that book-to-market, sales-to-price, earnings-to-price, and cash-flow-to-price are significant in explaining expected returns for Chinese equities, and thus conclude that value stocks generate returns superior to growth stocks. Our second major finding is that the superior performance of value stocks is related positively to investor uncertainty as proxied by their divergence of opinion.